Rancang Bangun Aplikasi Evaluasi Data Produksi Pada Dinas Kelautan dan Perikanan Kabupaten Situbondo - Alifi, Yusron; Setiyawan, Henry Bambang; Nurcahyawati, Vivine (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2017)
Marine and Fisheries Agency Situbondo is a government agency tasked to assist the Regent in exercising its authority in the marine and fisheries sector in Situbondo. These agencies often experience delays in reporting quarterly production report by the staff of statistical fields and also experienced difficulties in the evaluation report the results of marine and fisheries production by the Head of Evaluation and Planning. That is because often lost file reports and they are still in the form of table data. From the analysis of the above problems, it is known that the delay in reporting by the staff of statistical results in the evaluation process field production reports, it takes the application to keep records of production data, production data reporting and evaluation report every field of production conducted each quarter. The results of trials that have been done, the application can perform recording production data, production data reporting, and can provide production reports every field by displaying the target results and the results of their achievements so that these applications can help stakeholders at the Department of Marine and Fisheries Situbondo.